Emergency Resuscitation of Patients Enrolled in the US Diaspirin Cross-linked Hemoglobin (DCLHb) Clinical Efficacy Trial. Issue 1 (15th December 2014) - Sloan, Edward P.; Koenigsberg, Max; Weir, W. Brad; Clark, James M.; O'Connor, Robert; Olinger, Michael; Cydulka, Rita
Abstract: Introduction: Optimal emergent management of traumatic hemorrhagic shock patients requires a better understanding of treatment provided in the prehospital/Emergency Medical Services (EMS) and emergency department (ED) settings. Hypothesis/Problem: Described in this research are the initial clinical status, airway management, fluid and blood infusions, and time course of severely-injured hemorrhagic shock patients in the EMS and ED settings from the diaspirin cross-linked hemoglobin (DCLHb) clinical trial. Methods: Data were analyzed from 17 US trauma centers gathered during a randomized, controlled, single-blinded efficacy trial of a hemoglobin solution (DCLHb) as add-on therapy versus standard therapy. Results: Among the 98 randomized patients, the mean EMS Glasgow Coma Scale (GCS) was 10.6 (SD = 5.0), the mean EMS revised trauma score (RTS) was 6.3 (SD = 1.9), and the mean injury severity score (ISS) was 31 (SD = 17). Upon arrival to the ED, the GCS was 20% lower (7.8 (SD = 5.3) vs 9.7 (SD = 6.3)) and the RTS was 12% lower (5.3 (SD = 2.0) vs 6.0 (SD = 2.1)) than EMS values in blunt trauma patients ( P < .001). By ED disposition, 80% of patients (78/98) were intubated. Rapid sequence intubation (RSI) was utilized in 77% (60/78), most often utilizing succinylcholine (65%) and midazolam (50%). The mean crystalloid volume infused was 4.2 L (SD = 3.4 L), 80% of which was infused within the ED. Emergency department blood transfusion occurred in 62% of patients, with an average transfused volume of 1.2 L (SD = 2.0 L). Blunt trauma patients received 2.1 times more total fluids (7.4 L vs 3.5 L, < .001) and 2.4 times more blood (2.4 L vs 1.0 L, P < .001). The mean time of patients taken from injury site to operating room (OR) was 113 minutes (SD = 87 minutes). Twenty-one (30%) of the 70 patients taken to the OR from the ED were sent within 60 minutes of the estimated injury time. Penetrating trauma patients were taken to the OR 52% sooner than blunt trauma patients (72 minutes vs 149 minutes, P < .001). Conclusion: Both GCS and RTS decreased prior to ED arrival in blunt trauma patients. Intubation was performed using RSI, and crystalloid infusion of three times the estimated blood loss volume (L) and blood transfusion of the estimated blood loss volume (L) were provided in the EMS and ED settings. Surgical intervention for these trauma patients most often occurred more than one hour from the time of injury. Penetrating trauma patients received surgical intervention more rapidly than those with a blunt trauma mechanism. EP Sloan, M Koenigsberg, WB Weir, JM Clark, R O'Connor, M Olinger, R Cydulka .Emergency resuscitation of patients enrolled in the US diaspirin cross-linked hemoglobin (DCLHb) clinical efficacy trial .Prehosp Disaster Med .2015 ;30 (1 ):1 -8 .